Synthesis of 1-(4-Ethoxy-3-methoxybenzyl)-1,10-phenanthrolin-1-ium Bromide and Its Evaluation as Antiplasmodium through Heme Polymerization Inhibitory Activity (HPIA) Assay - Fitriastuti, Dhina; Alfiyah, Viny; Mustofa, Mustofa; Jumina, Jumina; Mardjan, Muhammad Idham Darussalam (Makara Journal of Science, 2021)
This study describes the development of N-benzyl-1,10-phenantrolinium salt as an antiplasmodium agent. The salt, that is, 1-(4-ethoxy-3-methoxybenzyl)-1,10-phenanthrolin-1-ium bromide, was prepared using vanillin as the starting material in four simple synthetic steps. First, the alkylation of vanillin using diethyl sulfate produced 4-ethoxy-3-methoxybenzaldehyde in 79% yield. Second, the reduction of the protected vanillin by NaBH4 through the grinding method allowed us to obtain 4-ethoxy-3-methoxybenzyl alcohol in 96% yield. Next, the bromination of the benzyl alcohol under solvent-free condition led to the formation of the corresponding benzyl bromide, which in turn underwent bimolecular nucleophilic substitution with 1,10-phenanthroline to produce the desired product, that is, 1-(4-ethoxy-3-methoxybenzyl)-1,10-phenanthrolin-1-ium bromide, in 58% yield. The evaluation of N-benzyl-1,10-phenantrolinium salt as an antiplasmodium agent was conducted through heme polymerization inhibitory activity (HPIA) assay. The results showed that the phenantroline salt and chloroquine displayed the HPIA half maximal inhibitory concentrations of 3.63 and 4.37 mM, respectively. Therefore, 1-(4-ethoxy-3-methoxybenzyl)-1,10-phenanthrolin-1-ium bromide displays desirable HPIA and has a great potential to be further developed as an antiplasmodium.